Evidence for Negative Effects of Elevated Intra-Abdominal Pressure on Pulmonary Mechanics and Oxidative Stress - I. Davarcı; M. Karcıoğlu; K. Tuzcu; K. İnanoğlu; T. D. Yetim; S. Motor; K. T. Ulutaş; R. Yüksel (The Scientific World Journal)
Objective. To compare the effects of pneumoperitoneum on lung mechanics, end-tidal CO2 (ETCO2), arterial blood gases (ABG), and oxidative stress markers in blood and bronchoalveolar lavage fluid (BALF) during laparoscopic cholecystectomy (LC) by using lung-protective ventilation strategy. Materials and Methods. Forty-six patients undergoing LC and abdominal wall hernia (AWH) surgery were assigned into 2 groups. Measurements and blood samples were obtained before, during pneumoperitoneum, and at the end of surgery. BALF samples were obtained after anesthesia induction and at the end of surgery. Results. Peak inspiratory pressure, ETCO2, and pCO2 values at the 30th minute were significantly increased, while there was a significant decrease in dynamic lung compliance, pH, and pO2 values in LC group. In BALF samples, total oxidant status (TOS), arylesterase, paraoxonase, and malondialdehyde levels were significantly increased; the glutathione peroxidase levels were significantly decreased in LC group. The serum levels of TOS and paraoxonase were significantly higher at the end of surgery in LC group. In addition, arylesterase level in the 30th minute was increased compared to baseline. Serum paraoxonase level at the end of surgery was significantly increased when compared to AWH group. Conclusions. Our study showed negative effects of pneumoperitoneum in both lung and systemic levels despite lung-protective ventilation strategy.